Secure transmission for NOMA downlink based on short packet communication - Gangcan SUN; Shaoke ZHAO; Wanming HAO; Zhengyu ZHU (Tongxin xuebao)
For the low-latency requirements of Internet of things (IoT) business, short packet communication (SPC) and non-orthogonal multiple access (NOMA) were combined to study the problem of secure transmission in the multi-user NOMA system with eavesdroppers.With the maximizing the secure throughput of weak uses as the objective, considering the user decoding error probability constraint, total power constraint and power allocation constraint, a low-complexity power allocation algorithm was proposed to realize secure transmission.In order to solve the problem caused by complex objective function formula and unreliable serial interference cancellation (SIC) technology, the proof that the compactness of the constraints was necessary to find the optimal solution.Under the constraint of maximum decoding error probability, the power constraint was transformed and calculated to obtain the strict limit of transmitting power for strong users, and the transmit power search set from base station to strong user was derived.Then, the one-dimensional search algorithm was used to allocate power resources to maximize the throughput of weak users.Simulation results prove that the proposed algorithm can effectively improve the security throughput of weak users in the system.